The Linking of Cultural Elements in EFL Learning as the Implication of Linguistic Relativity: A Framework Proposal (Proceeding Annual Conference on Madrasah Teacher, 2022)
Learning English as Foreign Language (EFL) is not only learning grammar, vocabulary, and pronunciation, but also learning its culture including song, film, food, building, and specific circumstances. This paper focuses on how Indonesian learners are introduced to foreign culture induced in the EFL teaching and learning. It is qualitative research employing the meta-analysis approach in exploring the culture content in EFL teaching and learning. The analysis helped in identifying some possible ways of teaching foreign culture to Indonesian learners. The result is in the form of proposed framework of EFL learning integrating the research shows that the learners are still lack of foreign culture contents taught through the EFL teaching and learning. The present research recommends that English teachers still need to explore many skills and approaches of teaching foreign culture especially to young learners and to improve methods of teaching EFL both English as foreign language and foreign culture.
Keywords: Culture; EFL Learning; Language Relativity